Enhancement of Biodiesel Production from Chicken Fat Using MgO and MgO@Na2O Nanocatalysts. Issue 1 (27th November 2020) - Bahador, Fariba; Foroutan, Rauf; Nourafkan, Ehsan; Peighambardoust, Seyed Jamaleddin; Esmaeili, Hossein
Abstract: Biodiesel was produced from chicken fat in the presence of MgO and MgO@Na2 O nanocatalysts via transesterification. The characteristics of MgO and MgO@Na2 O were examined using various analyses, including BET specific surface areas, energy‐dispersive X‐ray spectroscopy/mapping scanning electron microscopy, Fourier transform infrared spectroscopy, X‐ray diffraction, thermogravimetric analysis, and transmission electron microscopy. The maximum yields of biodiesel production using MgO and MgO@Na2 O nano‐catalysts were 95.17 and 95.22 %, respectively, which are significant biodiesel yields. 1 H NMR analysis was used to determine the molecular structure of the chicken fat oil and the produced biodiesel. Furthermore, the reusability of the catalysts was examined for up to six steps, showing that both catalysts can be used for up to four steps in biodiesel production. Abstract : Biodiesel was produced from chicken fat using MgO and MgO@Na2 O nanocatalysts. The highest biodiesel yields obtained using these nanocatalysts were 95.17 and 95.22 %, respectively, which are significant values. Both catalysts can be used for up to four steps in biodiesel production and both resulted in biodiesel with properties within the standard ranges of ASTM D6751 and EN 14214.